Integrating Batak Cultural Strategies and Values in Supporting Primary Education: A Systematic Literature Review - Yolanda Syeba Simatupang; Deni Setiawan; Nuni Widiarti; Arif Widiyatmoko (Journal of Innovation and Research in Primary Education, 2026)
This study aims to identify and analyze the cultural strategies employed by the Batak community in supporting primary education through a Systematic Literature Review (SLR) of relevant studies published between 2020 and 2025. Utilizing a qualitative approach with inductive thematic analysis, twenty-eight scholarly articles were examined to explore the relationship between Batak cultural values and educational practices. The results indicate that the Batak community’s educational achievements stem from eight interrelated strategies: (1) the philosophical foundation of “Anakkon Hi Do Hamoraon di Au” and the core values of “Hagabeon, Hamoraon, Hasangapon”; (2) the central role of the family as the first and foremost educational environment; (3) social support embedded in the kinship system Dalihan Na Tolu; (4) the influential role of Christianity and church institutions; (5) the integration of local wisdom into teaching and learning processes; (6) moral cultivation through traditional arts and rituals; (7) the merantau (migration) tradition as an opportunity for educational advancement; and (8) collaborative engagement among families, schools, communities, and religious institutions. The study concludes that the Batak community’s educational success is rooted not only in formal schooling but in deeply internalized cultural values, collective solidarity, and sustained familial commitment, offering a model for culturally grounded education in Indonesia.